Current progress on innate immune evasion mediated by Npro protein of pestiviruses - Wen, Shubo; Li, Xintong; Lv, Xiangyu; Liu, Kai; Ren, Jingqiang; Zhai, Jingbo; Song, Yang (Frontiers in Immunology, 2023)
Interferon (IFN), the most effective antiviral cytokine, is involved in innate and adaptive immune responses and is essential to the host defense against virus invasion. Once the host was infected by pathogens, the pathogen-associated molecular patterns (PAMPs) were recognized by the host pattern recognition receptors (PRRs), which activates interferon regulatory transcription factors (IRFs) and nuclear factor-kappa B (NF-κB) signal transduction pathway to induce IFN expression. Pathogens have acquired many strategies to escape the IFN-mediated antiviral immune response. Pestiviruses cause massive economic losses in the livestock industry worldwide every year. The immune escape strategies acquired by pestiviruses during evolution are among the major difficulties in its control. Previous experiments indicated that Erns, as an envelope glycoprotein unique to pestiviruses with RNase activity, could cleave viral ss- and dsRNAs, therefore inhibiting the host IFN production induced by viral ss- and dsRNAs. In contrast, Npro, the other envelope glycoprotein unique to pestiviruses, mainly stimulates the degradation of transcription factor IRF-3 to confront the IFN response. This review mainly summarized the current progress on mechanisms mediated by Npro of pestiviruses to antagonize IFN production. Thus, this article may be helpful to eventually develop feasible measures to prevent and control pestivirus infection.